Steinway Hall, Theodore Thomas' series of six symphony concerts, season 1872-73, Saturday eve'g, April 26th, 1873, sixth concert - Handel and Haydn Society (Boston, Mass.):::Contributor::::::::::::; Theodore Thomas Orchestra (New York, N.Y.):::Contributor:::::::::::: (United States; New York, NY, 2022)
Program for a concert at Steinway Hall, New York, by the Theodore Thomas Orchestra and the Handel and Haydn Society, which featured a performance of Beethoven's Ninth Symphony. Includes English translation of the text for the "Hymn to Joy."